RANCANG BANGUN REST API APLIKASI WESHARE SEBAGAI UPAYA MEMPERMUDAH PELAYANAN DONASI KEMANUSIAAN - Hasanuddin; Hari Asgar; Budi Hartono (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Donation activities are generally carried out through offline or direct media which of course makes it difficult for people to make donation transactions, because they have to come directly to the location of the donation service opening, besides that the reach of donors is limited if done offline. From these problems, an Application Programming Interface (API)-based donation transaction system was developed as Backend Development and implemented for Android-based Mobile and Websites. This research produces an API-based system with a REST architecture in terms of Backend Development to make it easier for the public to provide donation transactions and is applied to Android applications and websites as a user interface.